Particulate matter (PM10) and oxides of Nitrogen (NOx) each independently predict respiratory emergency outcomes - Seán Cournane; Richard Conway; Declan Byrne; Deirdre O'Riordan; Seamus Coveney; Bernard Silke (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Background: The impact of environmental air pollutants on the outcome of an emergency hospitalisation of respiratory patients has received limited study. We report on how levels of pollutants, particulate matter levels (PM10) and oxides of Nitrogen (NOx) infl uence hospital outcomes (30-day inhospital mortality). Methods: All emergency respiratory admissions (35,523 episodes, in 15,037 patients) were tracked between (2002-2015). Daily levels of PM10 and NOx from the hospital catchment area were correlated with outcome; univariate and multivariate logistic regression examined relationships between air pollution and outcome following adjustment for complexity. Results: There was a signifi cant reduction between 2002 and 2015 in levels of both PM10 20.4 to 12.9 (μg/m3) and NOx levels 76.5 to 38.2 (μg/m3). An increase in PM10 on the day of admission from lowest (Q1) to highest quintiles (Q5) increased the mortality risk- OR 1.31 (1.08-1.60) with absolute deaths rates increasing from 17.1% to 21.1%. Similarly, an increase in NOx at admission from lowest to highest quintiles increased mortality risk - OR 1.43 (1.17-1.74) and hospital mortality from 17.4% to 20.7%. Low  Socio-Economic status (SES) conferred a greater mortality risk, if admitted on days with higher levels of pollution - PM10 (p<0.01) Odds Ratio 1.02 (95% CI: 1.01, 1.04) and NOx (p=0.04) - OR 1.02 (95% CI: 1.00, 1.04). Conclusion: Levels of PM10 and NOx on the day of which respiratory patients had an emergency medical admission independently predicted the 30-day hospital mortality. Low SES status patients admitted on high pollution days had a worse outcome.